Decolonizing Universities pedagogy in creating space for an engaged teaching and learning - Nevhudoli, D. (South African Journal of Higher Education, 2025)
This article is grounded on how to decolonize pedagogy within the South African Universities, and the effective ways to create space for an active approach to education. The engagement, transfer, transformation, and extension of knowledge—including learning with diverse audiences through formal or informal arrangements—are all considered aspects of engaged teaching and learning in this article, and these learning includes community services learning, community based learning, or interprofessional learning. Capturing it from the literature on decolonizing pedagogy in institution of higher learning, the article probe into the issue of creating space for engaged teaching and learning around South African Universities. The article was qualitative in nature, participatory action learning research was used as methods and interviews were conducted from students and lecturers. Based on the main project about participatory evaluation of University program, an article about qualitative tracer studies and reviewed literatures,the article came up with the concepts and context of decolonization of pedagogy and the impact of decolonizing in creating space for teaching and learning. On this article the researcher argued that it is important to invent space for decolonial pedagogy into the overall teaching and learning practice. The article recommend that Universities should decolonize their curriculum , and they should be possibilities to have discipline of decolonial studies within each institution. Furthermore, the article advocates for the transformation of pedagogical approaches.